PENERAPAN EVIDENCE BASED NURSING TERAPI MEWARNAI TERHADAP PENURUNAN KECEMASAN AKIBAT HOSPITALISASI PADA ANAK USIA PRASEKOLAH DI RS BHAYANGKARA TK. I RADEN SAID SUKANTO - Isfia Aunillah Rahma Soleha (2022)
Hospitalization is a condition where children are required to undergo treatment in a hospital in according to health worker by subjective and objective data. Feelings of fear, sadness, and rebellion are responses to hospitalization, especially in preschool children who are cognitive immaturity, unable to adjust to new surroundings and are separated from their parents. Hospitalization makes children uncooperative during treatment, the presence of doctors, nurses so that the treatment process is lengthy and affects the growth and development. The purpose of this study was to reduce hospitalization anxiety with EBN coloring therapy in preschool age children. Respondents in this study were two people with one of the children being treated as patients who were given coloring therapy also nursing interventions in the same room. The intervention was carried out for 3 days with the frequency one time for 20 minutes. The measuring instrument used to measure the patient's anxiety level is the Hamilton Anxiety Rating Scale containing 14 questions related to anxiety. The results of the study on the third day showed a decrease against hospitalization anxiety patient experience with a comparison of the anxiety score on the first day 27 with moderate anxiety and anxiety scores on the third day 19 with mild anxiety. Therefore, coloring therapy can reduce hospitalization anxiety that occurs in preschool children.